Given that \( f(x)=x^{2}-13 x \) and \( g(x)=x+9 \), find (a) \( (f+g)(-5)=\square \) (b) \( (f-g)(-5)=\square \) (c) \( (f g)(-5)=\square \) (d) \( \left(\frac{f}{g}\right)(-5)=\square \) Question Help: Video Submit Question
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To solve the given problems, let's first evaluate the functions \( f(x) \) and \( g(x) \) at \( x = -5 \). 1. **Calculate \( f(-5) \)**: \[ f(-5) = (-5)^{2} - 13(-5) = 25 + 65 = 90. \] 2. **Calculate \( g(-5) \)**: \[ g(-5) = -5 + 9 = 4. \] Now we can solve each part: (a) **Calculate \( (f + g)(-5) \)**: \[ (f + g)(-5) = f(-5) + g(-5) = 90 + 4 = 94. \] So, \( (f + g)(-5) = 94 \). (b) **Calculate \( (f - g)(-5) \)**: \[ (f - g)(-5) = f(-5) - g(-5) = 90 - 4 = 86. \] So, \( (f - g)(-5) = 86 \). (c) **Calculate \( (fg)(-5) \)**: \[ (fg)(-5) = f(-5) \cdot g(-5) = 90 \cdot 4 = 360. \] So, \( (fg)(-5) = 360 \). (d) **Calculate \( \left(\frac{f}{g}\right)(-5) \)**: \[ \left(\frac{f}{g}\right)(-5) = \frac{f(-5)}{g(-5)} = \frac{90}{4} = 22.5. \] So, \( \left(\frac{f}{g}\right)(-5) = 22.5 \). To summarize: (a) \( (f+g)(-5) = 94 \) (b) \( (f-g)(-5) = 86 \) (c) \( (fg)(-5) = 360 \) (d) \( \left(\frac{f}{g}\right)(-5) = 22.5 \)